'They are all dead that I could ask': Indigenous Innovation and the Micropolitics of the Field in Twentieth-century Southern Africa. Issue 1 (February 2022) - King, Rachel; Bonneau, Adelphine; Pearce, David
Abstract : Recovering the agency, skill and innovation of archaeological field assistants from historical encounters is essential to interrogating processes of knowledge production, but is often hampered by access to appropriate archival sources and methods. We detail a field project from early twentieth-century Basutoland (modern-day Lesotho) that is unique both for its aim to salvage details of rock-art production as a dying craft and for its archive chronicling the project's intellectual journey from experiment to draft manuscripts to published work over more than three decades. We argue that critical historiographic attention to this archive offers a guide for examining the intimate dynamics of fieldwork and the effects of these micropolitics on the archaeological canon. We demonstrate how sustained attention to long processes of knowledge production can pinpoint multiple instances in which the usability of field assistants' scientific knowledge is qualified, validated, or rejected, and in this case how an African assistant is transformed into an ethnographic interlocutor. For rock-art studies especially, this represents a need for interrogating the epistemic cultures—not just the content—of foundational historical data.